E=(x-6)(x+5)+(x+2)(x-1)

Simple and best practice solution for E=(x-6)(x+5)+(x+2)(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for E=(x-6)(x+5)+(x+2)(x-1) equation:



=(E-6)(E+5)+(E+2)(E-1)
We move all terms to the left:
-((E-6)(E+5)+(E+2)(E-1))=0
We multiply parentheses ..
-((+E^2+5E-6E-30)+(E+2)(E-1))=0
We calculate terms in parentheses: -((+E^2+5E-6E-30)+(E+2)(E-1)), so:
(+E^2+5E-6E-30)+(E+2)(E-1)
We get rid of parentheses
E^2+5E-6E+(E+2)(E-1)-30
We multiply parentheses ..
E^2+(+E^2-1E+2E-2)+5E-6E-30
We add all the numbers together, and all the variables
E^2+(+E^2-1E+2E-2)-1E-30
We get rid of parentheses
E^2+E^2-1E+2E-1E-2-30
We add all the numbers together, and all the variables
2E^2-32
Back to the equation:
-(2E^2-32)
We get rid of parentheses
-2E^2+32=0
a = -2; b = 0; c = +32;
Δ = b2-4ac
Δ = 02-4·(-2)·32
Δ = 256
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$E_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$E_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{256}=16$
$E_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-16}{2*-2}=\frac{-16}{-4} =+4 $
$E_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+16}{2*-2}=\frac{16}{-4} =-4 $

See similar equations:

| 8-2x(6-3)=x | | x^2+14x+161=0 | | 6n+7-2n-14=15n+1 | | n^2+70n+275=0 | | (5)/y+7=(3)/y+3 | | d-2.5=13/10 | | w-4.88=5.45 | | 2(x-60=4 | | 5x^2+720=0 | | ×x17=187 | | 3/8t=12 | | (1/3)(x)-171=x | | 8/5+1/2t=9 | | 200m-100m+58200=60900-200m | | 38=90(x-23.5) | | 18=z-6 | | 8x-12=4x+36 | | 4x−6=−2x−16−2 | | 6-8x=7x-10-9 | | 4k−6=−2k−16−2 | | -1/3(9n+15)=22 | | x+6.3=5.3 | | 2x^+7x-4.5=0 | | x+6.3=-5.3 | | -(4x+12)^(1/3)=0 | | (b+4)(2b+1)=0 | | 3x^2+87=0 | | 1/2(6m-14)=5 | | 15-6=p | | y=y+2018 | | 6−3x=38 | | 12=-3b-b |

Equations solver categories